Sharī‘ah-compliant home financing in Malaysia: a case study of legal issues in Bai Bithaman Ājil contract - Oseni, Umar Aimhanosi; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2014)
Purpose – This paper provides a case study on a Sharī‘ah-compliant house loan contract based on the Bai Bitham Ajil (BBA) contract generally used by Islamic banks in Malaysia. The study emphasises the need to comply with the existing legal framework and execute relevant contracts in line with the Sharī‘ah resolutions of the Sharī‘ah Advisory Council of Bank Negara Malaysia without causing harm (ḍarar) to the customers or introducing uncertain elements or procedures (gharar) in the execution of the agreements.